Tinjauan Perbandingan Pengakuan Putusan Asing Dalam Hukum Indonesia dan Malaysia (RechtJiva, 2025)
The recognition and enforcement of foreign judgments are essential aspects of cross-border legal relations, especially in the context of globalization and increasing international legal interactions. This article aims to examine and compare the legal frameworks governing the recognition of foreign court decisions in Indonesia and Malaysia. This study employs a normative juridical method with a comparative legal approach. In Indonesia, the recognition of foreign judgments is regulated under the Reglement op de Rechtsvordering (Rv) and requires an exequatur process by the Supreme Court. Specifically for the recognition of foreign arbitration awards, Indonesia has ratified the 1958 New York Convention on the Recognition of Foreign Arbitration Awards. Meanwhile, in Malaysia, foreign judgments can be recognized through a reciprocal enforcement system based on the Foreign Judgments Act 1956 and common law principles. This comparison shows that Malaysia’s legal system is relatively more receptive to the recognition of foreign judgments than Indonesia, which still imposes several formal requirements. The study recommends regulatory reforms in Indonesia to better adapt to the dynamics of international law and to provide legal certainty for parties involved in cross-border disputes.